2021
DOI: 10.1158/1078-0432.ccr-21-0845
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I, Open-Label, Dose-Escalation Study of the OX40 Agonist Ivuxolimab in Patients with Locally Advanced or Metastatic Cancers

Abstract: Purpose: Stimulation of effector T cells is an appealing immunotherapeutic approach in oncology. OX40 (CD134) is a co-stimulatory receptor expressed on activated CD4+ and CD8+ T cells. Induction of OX40 following antigen recognition results in enhanced T-cell activation, proliferation, and survival, and OX40 targeting shows therapeutic efficacy in preclinical studies. We report the monotherapy dose-escalation portion of a multicenter, phase I trial (NCT02315066) of ivuxolimab (PF-04518600), a fully human immun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 50 publications
4
28
0
Order By: Relevance
“…Agonistic anti-OX40 antibodies showed an anti-tumor activity, associated with the infiltration and the proliferation of T cells and effector T cells at tumor sites, respectively [ 60 ]. A phase I trial evaluated the tolerability of ivuxolimab, a fully human immunoglobulin G2 agonistic monoclonal antibody specific for OX40, in a cohort of 52 patients with advanced cancer (melanoma: 2) [ 61 ]. A preliminary antitumor activity and the tolerability of ivuxolimab was reported.…”
Section: Resultsmentioning
confidence: 99%
“…Agonistic anti-OX40 antibodies showed an anti-tumor activity, associated with the infiltration and the proliferation of T cells and effector T cells at tumor sites, respectively [ 60 ]. A phase I trial evaluated the tolerability of ivuxolimab, a fully human immunoglobulin G2 agonistic monoclonal antibody specific for OX40, in a cohort of 52 patients with advanced cancer (melanoma: 2) [ 61 ]. A preliminary antitumor activity and the tolerability of ivuxolimab was reported.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, TNFRSF4 was overexpressed in HCC, associated with a more aggressive phenotype and the activation of multiple immunosuppressive pathways [ 36 ]. A phase I clinical research also supported that Ivuxolimab (a TNFRSF4 agonist) showed well tolerance and effective anti-tumor capacity in locally advanced or metastatic cancers, including HCC [ 37 ]. Consequently, treatment targeting TNFRSF4-TNFSF4 should be considered in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical efficacy of several agonists for 4-1BB and OX40 in combination with ICIs is currently under investigation. Recently published results from a clinical trial (NCT02315066) of OX40 agonist, alone or in combination with a 4-1BB agonist, have shown disease control in 56% of patients associated with an increase in CD4 + memory T cell proliferation and activation without dose-limiting toxicities ( 66 ). In a phase I study (NCT02554812), 26.1% of the patients who received combination treatment with the 4-1BB agonist utomilumab and pembrolizumab had complete or partial responses.…”
Section: Non-specific Targeting Of the Tmementioning
confidence: 99%